Herbal and Conventional Toothpastes Roles in Gingivitis Control in Orthodontic Patients - Stefani A. Dewi; Fadli Jazaldi; Benny M. Soegiharto (Faculty of Dentistry, Universitas Indonesia, 2013)
Orthodontic treatment with fixed appliance aims to improve esthetics and function of mastication and speech, however the components on a fixed appliance as bands, brackets and ligatures may increase the amount of plaque as the primary etiology of gingivitis. Objective: a double-blind study of randomized clinical trial was designed to investigate the effectiveness of herbal toothpaste against gingivitis as compared with conventional toothpaste in orthodontic patients with fixed appliance. Methods: Sixteen subjects before the application of fixed orthodonitc appliance was selected based on inclusion criteria. They were then randomized using block randomization method and divided into the test group and the control group. Gingival index of Löe and Sillness examined before brackets bonding and two weeks after. Paired t-test was used to compare the differences within the groups and unpaired t-test was used to compare the differences between groups at baseline and two weeks after. Results: There was a tendency of decreasing in gingival index but there were no significant differences between before and after the application of fixed appliance in the herbal toothpaste group. There was a tendency of increasing in gingival index and there were significant differences between before and after the application of fixed appliance in the conventional toothpaste group. There was significant differences between the two groups. Conclusion: There was significant difference between the two grouups, herbal indicates effectiveness in gingivitis control after the application of fixed orthodontic appliance, so it sould be used as an alternative natural based toothpaste in overcoming gigngivitis in orthodontic patients with fixed appliance.